Pharmacokinetic and pharmacodynamic principles - Henthorn, Thomas K.; Avram, Michael J. (Baillière's clinical anaesthesiology, 1991)
New drugs continue to be introduced into anaesthetic practice. Often innovation involves a modification of pharmacokinetic properties rather than pharmacologic activity. Besides selecting drugs based on its pharmacokinetic profile, the anaesthetist is increasingly faced with giving repetitive doses or continuous infusions of drugs to maintain the anaesthetic state. Accordingly, an understanding of pharmacokinetic and pharmacodynamic principles as well as factors which may cause patients or drugs to vary from one to another is essential. A description of the basic pharmacokinetic variables volume, elimination clearance, and half-life and their uses provides a foundation for introducing concepts of multicompartmental kinetics to clinical anaesthesia. Distribution clearance is defined as the ratio of drug transfer rate and drug concentration. Recent studies examining possible age-dependent changes in thiopentone distribution clearance are reviewed. During the onset of intravenous anaesthetic drug effect, pharmacokinetics are complicated by intravascular mixing and the interaction of drug with lung tissue. These processes influence early arterial drug concentrations and arterial-venous concentration differences. Combined pharmacokinetic-pharmacodynamic models were developed to characterize the time course of drug action and its relationship to plasma concentrations. More recent studies have used these models to detail differences between drugs and understand better the differences in dose response relationship among patients or groups of patients. However, the use of these models often requires a reliable continuous measure of drug effect on the central nervous system. Approaches to the use of computer-processed electroencephalograms have shown some promise in this regard, but still have sufficient limitations to make them impractical in the clinical setting and unusable in many investigational situations. Many anaesthetic drugs are metabolized by oxidative metabolic pathways actuated by specific proteins (e.g. P-450 enzymes). Several of these proteins are subject to common genetic variability that lead to marked variability in the performance of the oxidative pathway. While studies have suggested that alfentanil and midazolam are not subject to this variability in elimination, other drugs (e.g. diazepam) may be affected and require further studies. Pharmacokinetic and pharmacodynamic information have come together to permit the introduction of continuous administration of anaesthetic drugs. The bases for designing and implementing these techniques should be understood by anaesthetists, so that the advantages of newer drugs can be realized.